Search for the radiative decay D s + → γρ 770 + - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
Using 7.33 fb−1 of e+e− collision data samples collected with the BESIII detector at center-of-mass energies between 4.128 and 4.226 GeV, we search for the radiative decay Ds+→γρ770+ for the first time. A hint of Ds+→γρ770+ is observed with a statistical significance of 2.5σ. The branching fraction of Ds+→γρ770+ is measured to be (2.2 ± 0.9stat. ± 0.2syst.) × 10−4, corresponding to an upper limit of 6.1 × 10−4 at the 90% confidence level.